Murine leukemia virus p12 tethers the capsid-containing pre-integration complex to chromatin by binding directly to host nucleosomes in mitosis. - Madushi Wanaguru; David J Barry; Donald J Benton; Nicola J O'Reilly; Kate N Bishop (PLoS Pathogens)
The murine leukaemia virus (MLV) Gag cleavage product, p12, is essential for both early and late steps in viral replication. The N-terminal domain of p12 binds directly to capsid (CA) and stabilises the mature viral core, whereas defects in the C-terminal domain (CTD) of p12 can be rescued by addition of heterologous chromatin binding sequences (CBSs). We and others hypothesised that p12 tethers the pre-integration complex (PIC) to host chromatin ready for integration. Using confocal microscopy, we have observed for the first time that CA localises to mitotic chromatin in infected cells in a p12-dependent manner. GST-tagged p12 alone, however, did not localise to chromatin and mass-spectrometry analysis of its interactions identified only proteins known to bind the p12 region of Gag. Surprisingly, the ability to interact with chromatin was conferred by a single amino acid change, M63I, in the p12 CTD. Interestingly, GST-p12_M63I showed increased phosphorylation in mitosis relative to interphase, which correlated with an increased interaction with mitotic chromatin. Mass-spectrometry analysis of GST-p12_M63I revealed nucleosomal histones as primary interactants. Direct binding of MLV p12_M63I peptides to histones was confirmed by biolayer-interferometry (BLI) assays using highly-avid recombinant poly-nucleosomal arrays. Excitingly, using this method, we also observed binding between MLV p12_WT and nucleosomes. Nucleosome binding was additionally detected with p12 orthologs from feline and gibbon ape leukemia viruses using both pull-down and BLI assays, indicating that this a common feature of gammaretroviral p12 proteins. Importantly, p12 peptides were able to block the binding of the prototypic foamy virus CBS to nucleosomes and vice versa, implying that their docking sites overlap and suggesting a conserved mode of chromatin tethering for different retroviral genera. We propose that p12 is acting in a similar capacity to CPSF6 in HIV-1 infection by facilitating initial chromatin targeting of CA-containing PICs prior to integration.